Contrast-Enhanced, Fluoroscopically Guided Percutaneous Endoscopic Gastrostomy Tube Placement for the High-Risk Patient. Issue 1 (17th January 2022) - Prakash, Preeti; Su, Andrew; Mason, Leona; Tabibian, James H.
ABSTRACT: Percutaneous endoscopic gastrostomy (PEG) tubes can facilitate enteric feeding in patients with severe malnutrition but may be technically challenging to place. We present a man with disseminated tuberculosis and severe cachexia refractory to oral intake and nasogastric tube placement. PEG placement was initially deemed high-risk, through endoscopic, interventional radiologic, or surgical approach, because of severe cachexia and dilated bowel loops interposed between the abdominal wall and stomach. We describe a novel, minimally invasive technique to enhance safety and feasibility of PEG placement, which led to significant improvement in nutritional status and facilitated successful response to tuberculosis therapy.